Evaluasi UI pada Prototype Aplikasi “WeCare” Menggunakan Metode SUS (System Usability Scale) - Hammam Akmal Prathama; I Putu Gede Hendra Suputra (Informatics Department, Faculty of Mathematics and Natural Sciences, Udayana University, 2023)
The user interface is one of the most important factors in building an application. A good user interface has aspects of clarity, conciseness, easy recognition, responsiveness, consistency and has aesthetic content. Without careful preparation and design, certain applications cannot run optimally, and can even cause users to switch to other applications. To evaluate the user interface of an application, we can use many methods. One of them is SUS (System Usability Scale). This method provides a “quick and dirty”, reliable tool for measuring usability. The purpose of this study is to evaluate the quality of the User Interface design on the WeCare Application. Evaluation of the quality of the User Interface design will be carried out using the SUS or System Usability Scale method. Evaluation of quality on the usability aspect is carried out using the SUS questionnaire as an assessment standard. The results of this assessment will determine whether the UI design of the WeCare Application is appropriate or not. Based on the survey conducted, the calculation of the usability value of the WeCare application UI design that was tested using the SUS (System Usability Scale) method obtained an average SUS score of 78,33. By obtaining acceptability ranges in the acceptable category, the grade scale is in class B, and adjective rating is in the good category.